DESCRIPTION OF SOURCES IN BUKHARA IN THE 18TH AND 19TH CENTURIES - Zakirovna, Rajabova Rohila (International Journal of Psychosocial Rehabilitation, 2020)
In exploring our written spiritual heritage, conveying their content and essence to our people, the first President Islam Karimov stated: "It is time to seriously study the rare manuscripts that reflect the centuries- old experience of our ancestors, their religious, ethical and scientific views. Our ancestors have been leaders in the history of religious sciences, especially in the fields of hadith, jurisprudence, kalam and mysticism. Today, there is a great opportunity to study the life and works of Islamic scholars and to publish their works. All these good deeds that please our people are the result of wise, pathetic, far-sighted policy pursued by the President of the Republic. For the purpose of national self-awareness, preservation of historical memory, preservation, enrichment and research of the great written heritage, and popularization of cultural and spiritual values, the decision of the President of the Republic of Uzbekistan Sh.M.Mirziyoyev “On further improvement of preservation, study and introduction, of ancient written source” was accepted. The manuscripts work to promote the spirituality and enlightenment of the people, instill the taste of art, and increase their enthusiasm for science. The description of the manuscript works is a statement of their quality. In source studies description are used extensively. A brief, yet clear, and consistent description of the scientific features and external quality traits of a specific source or document is the description of the source.